2016
DOI: 10.1021/acs.est.6b01896
|View full text |Cite
|
Sign up to set email alerts
|

How Do Radionuclides Accumulate in Marine Organisms? A Case Study of Europium with Aplysina cavernicola

Abstract: In the ocean, complex interactions between natural and anthropogenic radionuclides, seawater, and diverse marine biota provide a unique window through which to examine ecosystem and trophic transfer mechanisms in cases of accidental dissemination. The nature of interaction between radionuclides, the marine environment, and marine species is therefore essential for better understanding transfer mechanisms from the hydrosphere to the biosphere. Although data pertaining to the rate of global transfer are often av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…13 Ku et al reported similar values with a mean concentration of uranium of about 3.3 µg/L. 14 Altogether uranium represents about 1% of the total radioactivity in seawater (the major contributor being 40 K accounting for more than 90%). 15 In seawater, the accumulation of several heavy metals in marine organisms has been widely studied at all trophic levels.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…13 Ku et al reported similar values with a mean concentration of uranium of about 3.3 µg/L. 14 Altogether uranium represents about 1% of the total radioactivity in seawater (the major contributor being 40 K accounting for more than 90%). 15 In seawater, the accumulation of several heavy metals in marine organisms has been widely studied at all trophic levels.…”
mentioning
confidence: 78%
“…39 The STXM methodology employed in this study was similar to that described previously. [40][41] The photon energy calibration of the monochromator was performed at the neon K-edge (867.3 eV). The STXM measurements were performed with a 25 nm zone plate in transmission mode and the ALS was operating in top-off mode with a beam current of 500 mA.…”
Section: Scanning Transmission X-ray Microscope (Stxm) Imagingmentioning
confidence: 99%
“…For these reasons sponges are considered biological indicators of environmental pollution such as radionucleotides 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of nuclear energy, the safe treatment and disposal of nuclear waste have restricted the further development of the nuclear industry. As one of the common radionuclide contaminants, uranium (U) mainly results from nuclear fuel production, which has been released into the ecological environment. Because of its long half-life, europium (Eu) is also considered to be a hazardous radioactive contaminant. , The accumulation and storage of a large volume of radioactive waste in the environment can be a threat to human health and result in various diseases due to its potential toxicity and carcinogenesis. , Therefore, many methods such as coagulation, electrodeposition, adsorption, reverse osmosis, and solvent extraction have been used for the elimination of radionuclides from the environment. Among these techniques, adsorption is a low cost and environmental friendly method, and a variety of adsorbents including activated carbon and clay mineral have been applied to remove radionuclides. , For example, the adsorption of U­(VI) on the layered double hydroxide/graphene material achieved 277.80 mg/g, showing a great advantage . Nevertheless, most of the existing studies only pay attention to the elimination of a single pollutant and neglect the existence of other radionuclides.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The accumulation and storage of a large volume of radioactive waste in the environment can be a threat to human health and result in various diseases due to its potential toxicity and carcinogenesis. 6,7 Therefore, many methods such as coagulation, electrodeposition, adsorption, reverse osmosis, and solvent extraction have been used for the elimination of radionuclides from the environment. 8−11 Among these techniques, adsorption is a low cost and environmental friendly method, and a variety of adsorbents including activated carbon and clay mineral have been applied to remove radionuclides.…”
Section: Introductionmentioning
confidence: 99%